Corneal Power Measurement Obtained by Fourier-Domain Optical Coherence Tomography: Repeatability, Reproducibility, and Comparison With Scheimpflug and Automated Keratometry Measurements. Issue 10 (October 2015) - Wang, Qinmei; Hua, Yanjun; Savini, Giacomo; Chen, Hao; Bao, Fangjun; Lin, Shishi; Lu, Weicong; Huang, Jinhai
Abstract : Purpose: To assess the repeatability and reproducibility of corneal power values obtained by a Fourier-domain optical coherence tomography (FD-OCT) system (RTVue) and to compare them with the values obtained by a Scheimpflug camera system (Pentacam HR) and by automated keratometry (IOL Master). Methods: Thirty-two eyes from 32 healthy subjects were included in this prospective study. Two experienced observers measured each eye 3 consecutive times with the Pentacam, IOLMaster, and RTVue centered on either the pupil or corneal vertex. The conventional keratometry equivalent (CKE) and anterior (Ka ), posterior (Kp ), and net (Kn ) corneal power values were determined. Results: The corneal power values obtained by the RTVue showed high repeatability (all intraclass correlation coefficient >0.96) and reproducibility (coefficient of variation <1.0%). Pupil-centered FD-OCT performed slightly better than corneal vertex-centered FD-OCT. Mean corneal values had higher reproducibly than any of the individual values. CKE, Ka, Kp, and Kn obtained by FD-OCT were 0.62 to 0.68 diopters (D), 0.70 to 0.76 D, 0.11 to 0.13 D, and 0.93 to 0.94 D higher than those obtained by the Pentacam HR, respectively. CKE and Ka obtained with the RTVue were also 0.60 to 0.74 D higher than those obtained with the IOLMaster, respectively. Conclusions: The corneal power measurements obtained by the RTVue FD-OCT system showed high repeatability and reproducibility. Measurements obtained by FD-OCT with pupil centration were more reproducible than those obtained by FD-OCT with corneal vertex centration. We recommend that pupil-centered FD-OCT be used in clinical applications. Neither RTVue versus Pentacam HR nor RTVue versus IOLMaster can be used interchangeably. Abstract : Supplemental Digital Content is Available in the Text.